Immunotherapy against glioblastoma using backpack‐activated neutrophils - Tatsuya Fukuta; Ninad Kumbhojkar; Supriya Prakash; Suyog Shaha; A. Da Silva‐Candal; Kyung Soo Park; Samir Mitragotri (Bioengineering & Translational Medicine)
Abstract Immune checkpoint inhibitors (ICIs) represent new therapeutic candidates against glioblastoma multiforme (GBM); however, their efficacy is clinically limited due to both local and systemic immunosuppressive environments. Hence, therapeutic approaches that stimulate local and systemic immune environments can improve the efficacy of ICIs. Here, we report an adoptive cell therapy employing neutrophils (NE) that are activated via surface attachment of drug‐free disk‐shaped backpacks, termed Cyto‐Adhesive Micro‐Patches (CAMPs) for treating GBM. CAMP‐adhered neutrophils (NE/CAMPs) significantly improved the efficacy of an anti‐PD1 antibody (aPD‐1) in a subcutaneous murine GBM model (GL261). A combination of NE/CAMPs and aPD‐1 completely regressed subcutaneous GL261 tumors in mice. The efficacy of NE/CAMPs against GBM was also tested in an orthotopic GL261 model. Neutrophil's ability to migrate into the brain was not affected by CAMP attachment, and intracerebral NE/CAMP accumulation was observed in mice‐bearing orthotopic GBM. The combination treatment of NE/CAMPs and aPD‐1 activated systemic immune responses mediated by T cells and showed improved therapeutic responses compared with aPD‐1 alone in the orthotopic GBM model. These results suggest that immunomodulation with NE/CAMPs offers a potential approach for the treatment of GBM by combination with ICIs.